Disability acceptance: Unconditional acceptance by parents of children with disabilities - Zaskia Andini Ramli; Rita Eka Izzaty; Siti Rohmah Nurhayati; Sheilla Varadhila Peristianto (Universitas Ahmad Dahlan, 2026)
Raising children with disabilities presents complex challenges that affect multiple aspects of family life. However, previous studies indicate that disability acceptance may serve as a protective factor for family resilience and quality of life in navigating these challenges. This study aims to explore the meaning of disability acceptance among parents of children with disabilities in Indonesia. A qualitative approach using a phenomenological design was employed, and data were analyze using Interpretative Phenomenological Analysis (IPA). Data were collected through semi-structured in-depth interviews with three parents in the Special Region of Yogyakarta, who were selected through purposive sampling. The findings identified six stages of acceptance, namely shock, denial, guilt, depression, rational acceptance, and spiritual acceptance. In addition, five superordinate themes describing the meaning of disability acceptance were generated: (1) transformation of meaning from a burden to a source of happiness, (2) acceptance as a repetitive and non-linear process, (3) adjustment of expectations and future planning based on the child’s potential, (4) acceptance grounded in moral values and unconditional love, and (5) spiritual acceptance as a form of surrender to destiny and life challenges. These findings indicate that disability acceptance is not only an emotional process but also a meaning-making construction influenced by personal values, family relationships, and spiritual beliefs. The study highlights the importance of culturally and spiritually sensitive support in facilitating parents’ disability acceptance processes.